Successful twin pregnancy in a patient with ulcerative colitis using azathoprine during conception - Casella, Giovanni (Research Institute for Gastroenterology and Liver Diseases, 2011)
Inflammatory bowel disease (IBD) frequently affects young patients of childbearing age. Treatments for inflammatory bowel disease include immunosuppressive, cytotoxic and surgical therapies. Azathioprine is frequently used to treat patients with steroid dependent IBD. We report the case of a patient with ulcerative colitis, treated with azathioprine prior to conception and during the subsequent pregnancy with the subsequent successful delivery of healthy twins. Although some potential risks indeed exist, the use of AZA may not be harmful to the mother or the fetus in many instances.